Secondhand cigarette smoke exposure causes upregulation of cerebrovascular 5‐HT1B receptors via the Raf/ERK/MAPK pathway in rats. (4th September 2012) - Cao, L.; Xu, C. B.; Zhang, Y.; Cao, Y. X.; Edvinsson, L.
Abstract Aim Cigarette smoke exposure increases the risk of stroke. Upregulation of 5‐hydroxytryptamine 1B (5‐HT1B) receptors is associated with the pathogenesis of cerebral ischaemia. This study examined the hypothesis that the expression of 5‐HT1B receptors is altered in brain vessels after secondhand smoke (SHS) exposure. Methods Rats were exposed to SHS in vivo for 200 min daily for 8 weeks. The contractile responses of isolated cerebral arteries were studies by a sensitive myograph. The mRNA and protein expression for 5‐HT1B receptors were examined by real‐time PCR, Western blot and immunofluorescence respectively. In addition, the phosphorylation of Raf/extracellular signal‐regulated kinase (ERK)/mitogen‐activated protein kinases (MAPK) pathway was evaluated. Results The results showed that SHS exposure shifted the 5‐HT1B receptor‐mediated concentration–contraction curve towards the left with a markedly increased maximal contraction. Furthermore, there were significant elevations in mRNA level and protein expression of 5‐HT1B receptors in SHS‐exposed rats. Immunostaining revealed that the 5‐HT1B receptors were localized to the smooth muscle cells of cerebral arteries. SHS was also found to induce the phosphorylation of Raf‐1 and ERK1/2 proteins. The administration of a Raf‐1 inhibitor GW5074 attenuated the 5‐HT1B receptor upregulation. Conclusion Secondhand smoke exposure upregulates cerebrovascular 5‐HT1B receptors in rats. The receptor upregulation is associated with Raf/ERK/MAPK activation.